Yamamoto coupling for the synthesis of benzophenes and acene-based cyclooctatetraenes - Rüdiger, Elias; Koser, Silke; Rominger, Frank; Freudenberg, Jan; Bunz, Uwe H. F. (Chemistry - a European journal, 2018)
Two TIPS-ethynylated dibromoacenes were used in a shotgun Yamamoto-reaction with 1,2-dibromobenzene or 4,5-dibromoveratrol. Four soluble benzononaphenes/benzoundecaphenes were isolated in satisfactory yields. Examples of tetracene- and pentacene-fused tetrabenzocyclooctatetraenes also isolated from this reaction are reported. All compounds were characterized by UV/Vis and fluorescence spectroscopy, cyclic voltammetry, X-ray crystallography as well as DFT and NICS calculations.
Gesehen am 25.04.2019